Let's use the distributive property.

PSKf(x)⋅g(x)=(−3x+2)(2x^{2} −5x−1) =(-3x+2)\times 2x^{2}-(-3x+2)\times 5x-(-3x+2)\times 1 =-3x\times 2x^{2}+2\times 2^{2}-(-3)x\times 5x-2\times 5x-(-3)x\times 1-2\times 1 =(-3*2)x^{3}+4x^{2}+(3\times 5)x^{2}-10x+3x-2 =-6x^{3}+4x^{2}+15x^{2}-10x+3x-2 =-6x^{3}+(4+15)x^{2}+(-10+3)x-2ZSK

\(\displaystyle{x}=-{6}{x}^{{{3}}}+{19}{x}^{{{2}}}-{7}{x}-{2}\)

PSKf(x)⋅g(x)=(−3x+2)(2x^{2} −5x−1) =(-3x+2)\times 2x^{2}-(-3x+2)\times 5x-(-3x+2)\times 1 =-3x\times 2x^{2}+2\times 2^{2}-(-3)x\times 5x-2\times 5x-(-3)x\times 1-2\times 1 =(-3*2)x^{3}+4x^{2}+(3\times 5)x^{2}-10x+3x-2 =-6x^{3}+4x^{2}+15x^{2}-10x+3x-2 =-6x^{3}+(4+15)x^{2}+(-10+3)x-2ZSK

\(\displaystyle{x}=-{6}{x}^{{{3}}}+{19}{x}^{{{2}}}-{7}{x}-{2}\)